PHYSIOLOGICAL BEHAVIOR AND YIELD OF RICE (ORYZA SATIVA) VARIETIES IN PRE-KHARIF AND KHARIF SEASON AT MID ALTITUDE OF MEGHALAYA - MUNDA, G.C.; DAS, ANUP; PATEL, D.P. (Annals of Agricultural Research, 2014)
A field experiment was conducted during 2004 to study the performance of pre-kharif and kharif rice in sunken beds under raised and sunken bed systems of cultivation. The treatment consisted of six varieties of rice in pre-kharif and five varieties in kharif season grown in sunken beds and other crops (maize & vegetables) on the raised beds. The crops were grown organically and the nutritional requirements of the crops were met through the washings of adjacent rabbit farm of the complex. Results revealed that all the rice varieties took longer duration for their maturity and produced higher number of tillers/plant in pre-kharif season compared to main kharif season. Significantly higher ripening ratio and grain yield was recorded in IR 64 (64%, 35.5 q/ha) followed by Krishna Hamsha (62.8% 27.3 q/ha) in pre-kharif season, whereas it was found maximum in Vivek Dhan 82 (70.3%, 37.18 q/ha) followed by VL Dhan 61 (69.6%, 28.95 q/ha) in kharif season. Significantly higher photosynthesis rate (29.5 u mol CO2 m-2s-1) and stomatal conductance (495.0 m mol m-2s-1) was observed in Vivek Dhan 82 during kharif season compared to other varieties. Chlorophyll Index was found significantly higher in Bhalum 1 followed by Vivek Dhan 82 in both the seasons. Highest transpiration rate was noticed in RCPL 1-87-8 followed by Vivek Dhan 82 in kharif season. Therefore, IR 64 and Krishna Hamsha in pre-kharif season and Vivek Dhan 82 and VL Dhan 61 in kharif season. Therefore, IR 64 and Krishna Hamsha in pre-kharif season and Vivek Dhan 82 and VL Dhan 61 in kharif season were found suitable under mid hills of Meghalaya.